Ty1‐fused protein‐body formation for spatial organization of metabolic pathways in Saccharomyces cerevisiae. Issue 3 (27th November 2017) - Han, Jong Yun; Song, Jae Myeong; Seo, Sung Hwa; Wang, Chonglong; Lee, Seung‐Goo; Lee, Hongweon; Kim, Seon‐Won; Choi, Eui‐Sung
Abstract: Metabolite production through a multistep metabolic pathway can often be increased by efficient substrate channeling created by spatial sequestration of the metabolic reactions. Here, Tya, a structural component in the Ty1 retrotransposon element that forms virus‐like particles (VLPs) in Saccharomyces cerevisiae, was used to spatially organize enzymes involved in a metabolic pathway into a multi‐enzyme protein body in yeast. As a proof of principle, Tya fusion to three key enzymes involved in biosynthesis of the isoprenoids farnesene and farnesol was tested to assess its potential to improve productivity. The Tya ‐ fusion protein resulted in three and fourfold increases in farnesene and farnesol production, respectively, as compared with that observed in a non‐fused control. Specifically, two‐phase partitioning fed‐batch fermentations of S. cerevisiae ATCC200589 overexpressing Tya‐fused enzymes (tHmg1, IspA, and α‐farnesene synthase) yielded 930 ± 40 mg/L of farnesene after 7 days. Additionally, we observed that the Tya‐fusion proteins tended to partition into particulate fractions upon 100, 000 g ultracentrifugation, suggesting the formation of large aggregates of protein bodies, with their particulate structure also observed by transmission electron microscopy. The dramatic increase in the biosynthetic productivity of metabolites via use of a Tya‐fusion protein suggested that this approach might be useful for the creation of multi‐enzyme complexes to improve metabolic engineering in yeast. Abstract : Tya, a structural component in the Ty1 retrotransposon element that forms virus‐like particles in Saccharomyces cerevisiae, was used to spatially organize enzymes involved in a metabolic pathway into a multi‐enzyme protein body in yeast. Tya fusion to three key enzymes involved in biosynthesis of the isoprenoids was tested to assess its potential to improve productivity. The Tya‐fusion protein resulted in 3‐ and 4‐fold increases in farnesene and farnesol production, respectively, as compared with that observed in a non‐fused control.